"I Know How to Advocate": Parents' Experiences in Advocating for Children and Youth Diagnosed With Autism Spectrum Disorder. (February 2022) - Smith-Young, Joanne; Chafe, Roger; Audas, Rick; Gustafson, Diana L
Background: Parental advocacy is a dynamic process that changes depending on the circumstances and needs of the child and parent. Communication deficits related to an Autism Spectrum Disorder (ASD) diagnosis often necessitate parental advocacy. This study describes how parents and caregivers of children and youth diagnosed with ASD engage in parental advocacy, the challenges they encounter and the advocacy skills they develop. Method: We used descriptive exploratory methodology informed by reflexive thematic analysis. The aim of the study was to explore advocacy in parents and caregivers of children and youth diagnosed with ASD. Results: We conducted in-depth, semi-structured interviews with 15 parents of children and youth with an ASD diagnosis living in 4 provinces of Atlantic Canada. The pathway in parents' advocacy journey included: (1) Expressing concerns; (2) Seeking help, assessment, and diagnosis; (3) Acquiring services; (4) Removing barriers; and (5) Developing advocacy skills. Conclusions: Our findings illustrate the process of parental advocacy, skill development, and the barriers parents encounter in advocating for their children with ASD. Future research might explore how health professionals can support parents' advocacy efforts.